Monetary policy according to HANK - Greg Kaplan; Benjamin Moll; Giovanni L. Violante (European Central Bank (ECB), 2016)
We revisit the transmission mechanism of monetary policy for household consumption in a Heterogeneous Agent New Keynesian (HANK) model. The model yields empirically realistic distributions of household wealth and marginal propensities to consume because of two key features: multiple assets with different degrees of liquidity and an idiosyncratic income process with leptokurtic income changes. In this environment, the indirect effects of an unexpected cut in interest rates, which operate through a general equilibrium increase in labor demand, far outweigh direct effects such as intertemporal substitution. This finding is in stark contrast to small- and medium-scale Representative Agent New Keynesian (RANK) economies, where intertemporal substitution drives virtually all of the transmission from interest rates to consumption.
Keywords: D14; D31; E21; E52; 330; consumption; earnings kurtosis.; heterogeneous agents; inequality; liquidity; monetary policy; new keynesian